Induced endometritis in early lactation compromises production and reproduction in dairy cows - A. Husnain; U. Arshad; M.B. Poindexter; R. Zimpel; M. Nehme Marinho; M.C. Perdomo; P. Fan; K.C. Jeong; C.D. Nelson; I.M. Sheldon; J.J. Bromfield; J.E.P. Santos (Journal of Dairy Science, 2023)
ABSTRACT: Objectives of this experiment were to study the effect of infusing utero-pathogenic bacteria to induce endometrial inflammation on productive performance in early lactation and subsequent reproduction. Although endometritis is associated with perturbed reproduction, numerous factors may contribute to the observed association. It was hypothesized that induced endometrial inflammation, resulting in localized and systemic inflammatory responses, compromises production and reproduction. Holstein cows without clinical disease and with less than 18% polymorphonuclear leukocytes (PMN) in endometrial cytology on d 31 ± 3 postpartum had their estrous cycle synchronized. Cows were blocked by parity and genomic breeding value for cow conception rate and, within block, assigned randomly to remain as untreated controls (CON; n = 37) or to receive an intrauterine infusion of 5.19 × 108 cfu Escherichia coli and 4.34 × 108 cfu Trueperella pyogenes during the luteal phase to induce endometrial inflammation (INF; n = 48). Endometrial cytology was taken on d 2 and 7 after treatment to evaluate the proportion of PMN. Rectal temperature, dry matter intake, and yields of milk and components were measured in the first 7 d after treatment. Blood serum was analyzed for concentration of haptoglobin. Leukocytes were isolated from blood on d 2 and 7 after treatment and on d 19 after artificial insemination (AI) and mRNA was quantified for a select group of genes. Cows received AI and reproduction was followed for 300 d postpartum. Bacterial infusion induced endometrial inflammation with increased proportions of PMN in the endometrial cytology on d 2 (4.4 ± 0.7 vs. 26.3 ± 2.8%) and 7 (10.9 ± 1.7 vs. 17.4 ± 2.1%) after treatment, resulting in increased mean prevalence of subclinical endometritis (>10% PMN; 23.3 ± 6.3 vs. 80.9 ± 5.1%). Rectal temperature did not differ between CON and INF, but the concentration of haptoglobin in serum tended to increase in INF compared with CON (113 ± 14 vs. 150 ± 16 µg/mL). Induced endometrial inflammation reduced yields of milk (44.9 ± 0.8 vs. 41.6 ± 0.8 kg/d), protein (1.19 ± 0.03 vs. 1.12 ± 0.03 kg/d), and lactose (2.17 ± 0.04 vs. 2.03 ± 0.04 kg/d) and tended to reduce dry matter intake (20.7 ± 0.5 vs. 19.4 ± 0.6 kg/d) in the first 7 d after treatment. Indeed, the reduction in milk yield lasted 4 wk. However, treatment did not affect yields of energy-corrected milk or fat because treatment with INF increased the concentration of fat in milk (3.54 ± 0.10 vs. 3.84 ± 0.10%). Induced endometrial inflammation reduced pregnancy per AI at all inseminations (33.4 ± 5.1 vs. 21.6 ± 3.7%) and the hazard of pregnancy (0.61; 95% CI = 0.36–1.04), which extended the median days open by 24 d. Blood leukocytes from INF cows had increased mRNA expression of the pro-inflammatory gene IL1B on d 2 and 7 after treatment, but reduced expression of the IFN-stimulated genes ISG15 and MX2 on d 19 after AI. Induced endometrial inflammation depressed production and caused long-term negative effects on reproduction in lactating dairy cows.